Rethinking the interface between tradition and modernity in post-apartheid South Africa through Zakes Mda’s the heart of redness - Mohale, Bongane; Montle, Malesela Edward; Mogoboya, Mphoto (Penerbit Universiti Kebangsaan Malaysia, 2023)
The interface between African tradition and modernity is one of the concerns of spirited debates in the post-colonial period. Although most African writers deal with it, relatively few have attempted to depict how tradition and modernity may both benefit African societies. Modernity has reached Africa and, thus, the African tradition cannot remain intact. The utmost global portent that distresses human social life is the impact of modernity. Therefore, the paper’s key objective is to delineate the degree of social impairment in the present-day Africa engendered by the interface between tradition and modernity. In Africa, modernity has not only influenced personal characteristics but also social, cultural, religious and the operation of establishments. Most believers of African tradition are very conventional, counterattacking the effects of modernity signalled by the colonial period, including the arrival of Christianity and Western teachings. This noted, the paper has utilised a qualitative research method and a textual analysis to critically scrutinise the impacts of the clash between tradition and modernity through the lens of the literary text, Heart of Redness (2000) by Zakes Mda. The findings from the study divulge the clash between African tradition and modernity has resulted in the erosion of many African traditional systems notwithstanding the dethronement of the colonial administration that empowered modernity at the expense of African traditional systems. The paper concludes that to reesseentialise African traditions, the remnants of colonialism should be successfully uprooted. This noted, this study will make a significant contribution to the rehabilitation of African traditions as it unravels the foundations and gatekeepers of modernity at the expense of African tradition.